Design of novel metal chalcogenide photoanodes supported with reduced graphene oxide for improvement of photoelectrochemical hydrogen evolution - BUDAK, ÖZLEM; KARACA ALBAYRAK, FATMA; ÖZKAYA, ALİ RIZA; KOCA, ATIF (My University, 2023)
Designing new photoanodes with high efficiency provides an effective route to develop photoelectrochemical hydrogen production. In this work, quaternary metal chalcogenides (CdZnMSSe (M: Ni, Cu, Mo)) and reduced graphene oxide- quaternary metal chalcogenide (RGO-CdZnMSSe) composite films are fabricated by simple one-step electrodeposition process. The photoanodes formed of quaternary metal chalcogenides and the incorporation of RGO in these composite films increase charge transfer capability and separation ability compared to cadmium-based photoanodes, leading to enhancement of the photoelectrochemical hydrogen production activity. A superior photocurrent response is recorded for RGO(0.25)-Cd0.8Zn0.2Ni0.2S0.2Se0.8 (5.34 mA cm−2 at 0.8 V vs RHE). In addition, the maximum ABPE value of RGO(0.25)-Cd0.8Zn0.2Ni0.2S0.2Se0.8 is determined as 1.95%. The achieved results offer a new insight into highly efficient next generation-photoanodes to convert solar energy to hydrogen.
Keywords: Kimya Mühendisliği ve Teknolojisi; Fizik; Astronomi ve Astrofizik; Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Physics; Astronomy and Astrophysics; Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Uzay bilimi; MÜHENDİSLİK, KİMYASAL; ASTRONOMİ VE ASTROFİZİK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; CHEMISTRY; SPACE SCIENCE; ENGINEERING, CHEMICAL; ASTRONOMY & ASTROPHYSICS; Genel Kimya; Fizik Bilimleri; Genel Kimya Mühendisliği; Genel Fizik ve Astronomi; General Chemistry; Physical Sciences; General Chemical Engineering; General Physics and Astronomy; Electrodeposition; Photoelectrochemical performance; Quaternary metal chalcogenide thin films; Reduced graphene oxide